Determinants of Coffee Marketing: The Case of Coffee Growers and Suppliers in Kafa Zone, Ethiopia - Seyfe Fikre; Mulgeta Niguse (Britain International for Academic Research (BIAR-Publisher), 2023)
Coffee is the most important cash crop commodity to the Ethiopian economy. About 15 million peoples have been directly or indirectly deriving their livelihoods from coffee product. The coffee marketing chain in Ethiopia is weak in terms of linkages with industry, agro processing and value-addition downstream of farms, provision of farm inputs upstream, and poor post-harvest operations, storage, distribution and logistics. This has resulted in poor performance of the sector mainly on the targets of export earnings that the government has planned to attain. This study aims at examining the basic factors that determine coffee marketing on growers and suppliers in Keffa Zone Gimbo woreda. Purposive and two stage random sampling technique were used and the data was collected from 78 coffee producers and supplier. The data collection tools used for the study were interview and observation on the determinants of coffee marketing in the coffee producers as well as coffee suppliers in the study area. Tobit regression was used to identify the main determinants of coffee marketing and to identify the extent of each factor on coffee producer and supplier. The result indicates expansion of illegal trade was significantly hinder the coffee market participation and reduce the amount of coffee supplied to the market. On the other hand access to market, training access, transportation access, farming experience and land size allotted to coffee production was found positive and significant. In addition restricted time schedule to buy and sell coffee product was also discourage the coffee marketing. Restricted time schedule sometimes resulted in oversupply of coffee product and low market price. Therefore, all responsible bodies like federal and regional government, kaffa zone, traders, investors, ECX, NGOs etc. should work together in order to make the society beneficiary from marketing of coffee.